2020
DOI: 10.1182/bloodadvances.2019000845
|View full text |Cite
|
Sign up to set email alerts
|

Eμ and 3′RR transcriptional enhancers of the IgH locus cooperate to promote c-myc–induced mature B-cell lymphomas

Abstract: Key Points Transcriptional cooperation between IgH Eμ and 3′RR enhancers is found during B-cell lymphomagenesis in IgH-c-myc mice. Transcriptome analysis reveals wide similarities between human and mouse Burkitt B-cell lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…′ to C µ with E µ deletion (namely iMycC µ mice), thus modeling human sporadic BL, confirmed that 3'RR alone is sufficient to deregulate c-myc in the B-cell lineage and to induce B-cell lymphoma development (70). Taken altogether, these KI models carrying c-myc at the IgH locus are prone to B-cell lymphomas of various penetrance, kinetics, and fate as recently reported in a study comparing the three mouse models (71). The lymphoma signatures are also heterogeneous even comparing lymphomas from a specific KI, mirroring the genomic differences observed between the various subtypes of human mature B-cell lymphomas and those previously reported with the model of transgenic E µ -Myc mice.…”
Section: The Combination Of E µ and 3'rr Cis-transcriptional Enhancersupporting
confidence: 71%
“…′ to C µ with E µ deletion (namely iMycC µ mice), thus modeling human sporadic BL, confirmed that 3'RR alone is sufficient to deregulate c-myc in the B-cell lineage and to induce B-cell lymphoma development (70). Taken altogether, these KI models carrying c-myc at the IgH locus are prone to B-cell lymphomas of various penetrance, kinetics, and fate as recently reported in a study comparing the three mouse models (71). The lymphoma signatures are also heterogeneous even comparing lymphomas from a specific KI, mirroring the genomic differences observed between the various subtypes of human mature B-cell lymphomas and those previously reported with the model of transgenic E µ -Myc mice.…”
Section: The Combination Of E µ and 3'rr Cis-transcriptional Enhancersupporting
confidence: 71%
“…Another model of c-Myc driven Burkitt's lymphoma is one driven solely by the 3' regulatory region of the IgH locus rather than the Eµ enhancer. This model results in the development of B-cell malignancies with a mature B-cell phenotype in contrast to the Eµ model wherein a pro-B phenotype is predominant (27,28).…”
Section: Need For the Development Of New Murine Models For B-cell Malignanciesmentioning
confidence: 97%
“…Existing studies on Ig enhancer polymorphisms were done on a very small scale and there are conflicting conclusions about their potential role in diseases [ 119 , 120 ]. However, mutations in Ig heavy enhancer have been previously implicated in B-cell lymphomas [ 121 ]. The 3′ regulatory region and the switch regions of human and murine Ig loci have been shown to contain hotspots for oestrogen receptor binding [ 122 , 123 ].…”
Section: Enhancers and Their Role In Regulating Ig Expressionmentioning
confidence: 99%